Hepatopulmonary syndrome secondary to metabolic associated fatty liver disease in childhood — novel treatment with growth hormone replacement therapy: a case report and systematic review of literature - Choe, Yunsoo; Lee, Yun Jeong; Lee, Young Ah; Ko, Jae Sung; Shin, Choong Ho (Frontiers in Endocrinology, 2024)
Objective: Hepatopulmonary syndrome (HPS) is a rare complication of metabolic associated fatty liver disease (MAFLD) occurring subsequent to hypopituitarism, often developing after resection of hypothalamic or pituitary tumors. The aim of this study is to report an illustrative case of an HPS patient who was successfully treated with growth hormone replacement therapy, without liver transplantation which is conventionally regarded as the only treatment option. Additionally, we conducted a comprehensive review of published case reports of HPS in the pediatric population.We systematically searched literature databases to identify case reports and case series of HPS associated with hypopituitarism diagnosed in childhood. The search included MEDLINE/PubMed, Scopus, Embase, and Google Scholar from 1990 to 2023. The review process adhered to the PRISMA checklist for comprehensive reporting and methodological transparency.Results: An 18-year-old female, who had been followed up for MAFLD after craniopharyngioma resection, presented with cyanosis and progressive dyspnea. She was diagnosed with severe degree of HPS. The patient began treatment with recombinant human growth hormone, leading to a significant improvement in respiratory symptoms within 3 months, and normalization of lung shunt ratio after six months of therapy. In our systematic review, nine patients from nine studies across six countries were identified. The median age at diagnosis of hypopituitarism was 10.5 years (range 1-16 years), and HPS was diagnosed at a median interval of 7 years later (range 0-26 years). Half of the patients had not received growth hormone therapy after being diagnosed with hypopituitarism, which subsequently led to the diagnosis of HPS. Three patients underwent liver transplantation, but nonalcoholic steatohepatitis recurred in all cases. Six patients were successfully treated with growth hormone replacement therapy without undergoing liver transplantation.Conclusions: HPS can occur in pediatric patients with MAFLD who have undergone resection of the tumor in the hypothalamus or pituitary gland. Our findings suggest that growth hormone replacement therapy can be a possible alternative to liver transplantation for HPS patients. However, further investigations need to be performed to validate the efficacy of growth hormone treatment in different causes of HPS cases.